Sistem Informasi Geografis Berbasis Web Pemetaan Puskesmas di Baturaja Timur (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to develop a web-based Geographic Information System (GIS) that maps the locations of community health centres in the Baturaja area to make it easier for the community and stakeholders to access health service information. The research method used was descriptive with a system development approach. The research stages included a literature study to obtain a theoretical basis, data collection through field observation and documentation to obtain location data and information on health centre facilities, database and system interface design, and implementation of a web-based GIS using digital maps. The system was then functionally tested to ensure that all features worked as required. The results of the study show that web-based GIS is capable of displaying health centre locations interactively, presenting facility information and service coverage clearly, and increasing the effectiveness and speed of searching for health service information. Thus, this web-based GIS has the potential to support information dissemination and decision-making in the health sector in the Baturaja region.